Pursuing human security in Africa through developmental peace missions : ambitious construct or feasible ideal? - Olivier, Laetitia (Stellenbosch : Stellenbosch University, 2008)
Thesis (MMil (Military Sciences. School for Security and Africa Studies))--Stellenbosch University, 2008.